2021
DOI: 10.3390/cancers13174278
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Inhibition of the Mitochondrial Pyruvate Carrier on the Tumor Extracellular pH as Measured by CEST-MRI

Abstract: (1) Background: The acidosis of the tumor micro-environment may have profound impact on cancer progression and on the efficacy of treatments. In the present study, we evaluated the impact of a treatment with UK-5099, a mitochondrial pyruvate carrier (MPC) inhibitor on tumor extracellular pH (pHe); (2) Methods: glucose consumption, lactate secretion and extracellular acidification rate (ECAR) were measured in vitro after exposure of cervix cancer SiHa cells and breast cancer 4T1 cells to UK-5099 (10 µM). Mice b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 58 publications
0
16
0
Order By: Relevance
“…Furthermore, the CEST-pH approach was able to detect changes in tumor pHe in a mammary tumor model (4T1) following treatment with a mitochondrial pyruvate carrier (MPC) inhibitor (UK-5099), where 31 P NMR spectroscopy did not detect any significant changes. In particular, analysis of histograms of distributions of pHe values revealed that a small part of the tumors was affected by extracellular acidification [46]. In addition to response studies, improvements in imaging acquisitions and volume coverage were achieved with multislice CEST acquisitions allowing a more comprehensive and extensive visualization of tumor extracellular pH [47][48][49][50].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the CEST-pH approach was able to detect changes in tumor pHe in a mammary tumor model (4T1) following treatment with a mitochondrial pyruvate carrier (MPC) inhibitor (UK-5099), where 31 P NMR spectroscopy did not detect any significant changes. In particular, analysis of histograms of distributions of pHe values revealed that a small part of the tumors was affected by extracellular acidification [46]. In addition to response studies, improvements in imaging acquisitions and volume coverage were achieved with multislice CEST acquisitions allowing a more comprehensive and extensive visualization of tumor extracellular pH [47][48][49][50].…”
Section: Discussionmentioning
confidence: 99%
“…As the effects of syrosingopine on tumor cell proliferation were more pronounced on MDA-MB-231 cells than on FaDu cells, in vivo studies were carried out on the MDA-MB-231 tumor model to measure potential changes in pHe and in tumor growth. CEST-MRI was applied using a protocol adapted from our previous work on mitochondrial pyruvate carrier (MPC) inhibition [24]. The administration pattern of syrosingopine was inspired by the work of Benjamin et al [17,18].…”
Section: In Vivo Phe Measurements With Cest-mrimentioning
confidence: 99%
“…CEST Calibration In Vitro All experiments were performed on an 11.7T Biospec MRI (Bruker, Ettlingen, Germany). Calibration studies were performed as previously described [24]. CEST acquisitions were acquired with a 1 H volume coil with a 40 mm inner diameter.…”
Section: Tumor Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…It could inhibit the mitochondrial acetone carrier (MPC) by binding to C54 of MPC2 in a covalent reversible manner with a low dissociation rate of the inhibitor-carrier complex, which assists the transport of pyruvate across the inner mitochondrial membrane, plays a key role in the metabolism of carbohydrates, lipids and amino acids, and then blocks the entry of pyruvate into mitochondria, weakening mitochondrial oxidative phosphorylation (OXPHOS) and triggering aerobic glycolysis [ 1 , 3 – 5 ]. Compared with parental cells, UK-5099-treated tumor cells also showed stronger invasive ability [ 6 ], and a significant decrease in tumor pHe of 0.22 units in UK-5099 treated mice [ 7 ]. Moreover, UK-5099 inhibited the oxidation of pyruvate in rat heart mitochondria in a nonlinear inhibitory kinetic manner [ 2 ].…”
Section: Introductionmentioning
confidence: 99%